Selfish mining detection scheme based on the characters of transactions - Heli WANG; Qiao YAN (网络与信息安全学报)
Selfish mining is an attack strategy in Proof-of-Work based blockchains, where attackers withhold their mined blocks to intercept the awards of other honest miners, resulting in higher profitability.This attack undermines the incentive compatibility of Proof-of-Work.Although there are various studies from researchers in recent years, there is no effective detection scheme as the vulnerability of blockchain in propagation delay makes it challenging to distinguish the attackers from honest miners.A scheme for selfish mining detection was introduced.In this scheme, a state value was assigned to the new block based on transaction amount and the transaction fee of the block.By analyzing the relationship between state value and transaction characteristics, we can determine if the block was mined by a selfish miner.The scheme is verified by an experiment with an accuracy of 86.02%.